The prevalence of psychosocial risk factors in acute myocardial infarction - Govender, Denishan (My University, 2021)
Background: Psychosocial risk factors have traditionally been known to be common in patients diagnosed with acute myocardial infarction (MI). Although well studied in developed nations the role of psychosocial risk factors in patients with myocardial infarction in the African continent is extremely sparse. Aims: The aim of this research study was to assess the prevalence of depression, anxiety and stress in patients presenting with acute MI and to compare the prevalence of these psychosocial factors with matched controls without cardiac disease at a large public academic hospital in Johannesburg, South Africa. Methods: A case-control prospective study was conducted to determine prevalence of mild to extremely severe levels for each of the three emotional states (depression, anxiety and stress) by using the Depression Anxiety Stress Scale (DASS) as well the INTERHEART Questionnaire. Each of the study patients were matched with control patients by race, sex and with no more than 5 years difference in age. A total of 106 patients were included as study patients and matched with 106 control stable patients without myocardial infarction Questionnaires were used to interview patients during the same admission. Stressful life events were analysed in two ways: as individual and grouped life events and each was coded as a separate category. Results: Majority of patients in the case (acute MI) and control (non-MI) groups were between 51-60 years. More than 70% of the patients were over the age of 50 years. Over 80% of study patients in both groups were males. In patients with acute MI, over 85% of patients reported no depressive features and 91% did not have features of anxiety, in contrast to what was found in the INTERHEART study, findings which were similar to the control group. Self-reported stress profile of the two groups differed enormously; only 4.7% of MI patients reported normal stress levels, compared to 96.2% of controls. Stress graded as severe or very severe was found in 39.6% of patients with MI with the odds of an MI being extremely high in the group with mild to extremely severe stress compared to those with normal stress (Odds ratio: 515; 95% CI 134 to >999; p=0.0001). Conclusions: Depression and anxiety were not significantly more prevalent in patients with acute myocardial infarction as compared to matched controls. However, stress as assessed by both methodologies was significantly higher in patients with acute MI as compared to matched controls. Considering the increase in prevalence of traditional coronary heart disease risk factors recently, it is necessary that attention should also be focused on psychological risk factors and its preventive measures
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfillment of the requirements for the degree of Master of Medicine in Internal Medicine, 2021